Comparison of Physical and Chemical Changes of Dried Berries Fruits Powders from Spray and Freeze Drying - Alwani Hamad; Afwa Hayuningtyas; Pinyapat Jitphongsaikul (Universitas Wahid Hasyim, 2022)
The different drying methods for preserving fruits may affect fruits' physical and chemical properties, especially dried berries. The expected drying techniques include Spray Drying (SD) and Freeze Drying (FD). The physical characteristics, such as color, taste/odor, and thermal properties, have changed during the process. The higher temperatures in spray drying may affect the phytochemical compounds that will change the final nutritional value. The juice taste and color of berries powders that FD produces are better than SD. However, the morphology of powder that resulted from SD is better. Also, the losses of phenolic compound and anthocyanin content of dried berries produced from SD are much lower than FD. Therefore, the choices of higher quality dried berries can be produced by FD that are suitable to preserve the phytochemical compounds that have health benefits.